Synthesis, crystal structure and spectroscopy studies of a new non-centrosymmetric organic cation nitrate (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The synthesis, crystal structure and spectroscopic studies are reported for the salt m-anisidinium nitrate. A single-crystal X-ray investigation has shown that this compound crystallizes in the non-centrosymmetric space group Cc with the lattice parameters: a = 5.744(3) Å, b = 14.968(6) Å, c = 10.178(4) Å; b = 96.910(7)o; V = 868.6(6)Å3 ; Z = 4. The structure was solved from 1973 independent reflections with R1 = 0.033 and wR2 = 0.088. The hydrogen atoms of the protonated amine undergo hydrogen bonding interactions with oxygen atoms of three different nitrate anions forming 2-dimensional sheets. Solution NMR results are consistent with the X-ray structure. A measured optical band gap of 3.35eV indicates m-anisidinium nitrate is a wide-band-gap dielectric material.